TRANSFORMATIONS OF THE NATIONAL ECONOMY OF UKRAINE IN THE PLANE OF DEVELOPMENT OF THE MAIN CLUSTERS ON THE BASIS OF INDUSTRY 4.0 IN THE POST-COVID PERIOD (INNOVATIVE ECONOMY, 2020)
Voitko S.V., Frolova A.A. TRANSFORMATIONS OF THE NATIONAL ECONOMY OF UKRAINE IN THE PLANE OF DEVELOPMENT OF THE MAIN CLUSTERS ON THE BASIS OF INDUSTRY 4.0 IN THE POST-COVID PERIODPurpose. The aim of the article is to identify the possibility of using the best practices of the Marshall Plan on the basis of Industry 4.0 during the deep social and economic crisis for the effective functioning of the economic system in the new realities of the post-COVID period.Methodology of research. The following methods are used to achieve this goal: abstract and logical – in the study of the essence of categories and concepts in the field of Industry 4.0; comparative and economic – in the analysis of domestic and world experience of the transition to production in the new realities of the post-COVID period on the basis of Industry 4.0; statistical analysis and generalization – to process an array of statistical and empirical data and formulate the relevant conclusions of the study.Findings. The need to adapt the mechanisms of economic systems to the new reality of the post-COVID period for the development of the social and economic sphere of the countries is determined. The need to analyze changes in consumer habits and preferences during the global economic crisis of the early third decade of the XXI century, which is due to quarantine measures, is established. It is proposed to carry out the transformation of social and economic systems for developing countries on the basis of the “Marshall Plan” and using the technologies of Industry 4.0.It is proved that for Ukraine it is necessary to concentrate efforts in the main clusters of the national economy. The expediency of concentrating efforts in the development of Ukraine's economy on knowledge-intensive production, on increasing the scientific and technological components in all clusters of the economy, as well as on the need to take into account best practices in the implementation of the “Marshall Plan”.Originality. The substantiation of the possibilities of transformation of the national economy in the conditions of the global social and economic crisis with the use of the Marshall Plan on the basis of Industry 4.0 and the use of data on the development potential of the main clusters of the economy was further developed.Practical value. The obtained results of the research can be used to identify opportunities for the development of the main clusters of the economy of Ukraine on the basis of Industry 4.0 and the means of the “Marshall Plan”.Key words: major economic clusters, Industry 4.0, the post-COVID period, the “Marshall Plan”.
Keywords: Key words; major economic clusters; Industry 4.0; the post-COVID period; the “Marshall Plan”.